2016
DOI: 10.1111/1475-679x.12154
|View full text |Cite
|
Sign up to set email alerts
|

IRS Attention

Abstract: We study how public and private disclosure requirements interact to influence both tax regulator enforcement and firm disclosure. To capture IRS enforcement activities, we introduce a novel data set of IRS acquisition of firms' public financial disclosures, which we label IRS attention. We examine the implementation of two new disclosure requirements that potentially alter IRS attention: FIN 48, which increased public tax disclosure requirements, * The Ohio State University; † University of North Carolina at C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(84 citation statements)
references
References 59 publications
(85 reference statements)
4
70
0
4
Order By: Relevance
“…For example, recent evidence suggests that the IRS finds FIN 48 disclosures in the United States useful for tax enforcement purposes (Bozanic et al. []). In a similar manner, mandatory subsidiary disclosures could provide new information to tax authorities in the United Kingdom and other jurisdictions.…”
Section: Background and Hypothesismentioning
confidence: 99%
“…For example, recent evidence suggests that the IRS finds FIN 48 disclosures in the United States useful for tax enforcement purposes (Bozanic et al. []). In a similar manner, mandatory subsidiary disclosures could provide new information to tax authorities in the United Kingdom and other jurisdictions.…”
Section: Background and Hypothesismentioning
confidence: 99%
“…First, banks might reduce their extent of profit shifting since tax authorities have more information at hand to audit tax-aggressive banks more efficiently. As Bozanic et al (2017) have shown, tax authorities actually make use of tax-related disclosures in financial statements in case they contain incremental information to the tax return data. Second, increased public scrutiny might induce banks to voluntarily pay their "fair share of taxes".…”
Section: Prior Literature and Hypothesesmentioning
confidence: 99%
“…Aqui, identificam-se tanto investigações teóricas (De Simone, Sansing & Seidman, 2013) como empíricas (Bozanic, Hoopes, Thornock & Williams, 2017). As pesquisas centram-se, predominantemente, no papel das autoridades fiscais na inibição da Agressividade Tributária (Hoopes, Mescall & Pittman, 2012), a distância à autoridade fiscal da sede física do sujeito passivo (Kubick, Lockhart, Mills & Robinson, 2017), a atuação dos reguladores financeiros, tais como o monitoramento da SEC, (Hope, Ma & Thomas, 2013; e o papel da transparência fiscal (Beck & Lisowsky, 2014;Henry, Massel & Towery, 2016).…”
Section: Restrições Dos Gatekeepersunclassified
“…No Brasil poder-se-ia tentar investigar qual o efeito das ações das auditorias tributárias na agressividade fiscal? (Bozanic et al, 2017;Hoopes et al, 2012;.…”
Section: Relação Entre O Risco Fiscal E a Agressividade Tributáriaunclassified